The assessment of array comparative genomic hybridization in complex karyotype analyses - Bystřická, D; Zemanová, Z; Březinová, J; Gančarčíková, M; Grosová, L; Sárová, I; Izáková, S; Berková, A; Michalová, K (Folia biologica, 2010)
Molecular-cytogenetic methods were used to analyse and specify complex genome rearrangements in malignant cells. Twelve samples of bone marrow cells were collected from patients with myelodysplastic syndromes (MDS). The complex karyotypes were examined by multicolour fluorescence in situ hybridization (mFISH), high-resolution multicolour banding (mBAND) and array comparative genomic hybridization (aCGH). For aCGH, DNA was isolated from fixed bone marrow cells in methanol and acetic acid and amplified by whole-genome amplification. Three samples were analysed by the oligonucleotide array NimbleGen on the basis of full service. BAC-based Haematochips (BlueGnome) were used for the other nine samples. Sensitivity and detection limits of both methods were compared. The results obtained by mFISH/mBAND were in most cases confirmed by the microarray technique. aCGH detected 43 unbalanced chromosomal changes that were also identified by classical cytogenetics and FISH. Moreover, aCGH discovered 14 additional changes. Cryptic amplifications and deletions were characterized with a resolution of 0.5 Mb. In one bone marrow sample with suspected monosomy 5 detected by conventional cytogenetic analysis, aCGH revealed a 22.3 Mb region of chromosome 5 inserted in another autosome within the complex karyotype. Amplified DNA was successfully used for aCGH in 11 out of 12 cases, improving resolution of unbalanced chromosomal aberrations. The combination of both approaches brought more detailed description of complex karyotypes and is highly recommended.
Keywords: cytogenetika; dospělí; Comparative Genomic Hybridization; Gene Rearrangement; Karyotyping; Humans; Myelodysplastic Syndromes; hybridizace in situ fluorescenční; Cytogenetics; srovnávací genomová hybridizace; lidé; myelodysplastické syndromy; In Situ Hybridization, Fluorescence; karyotypizace; Adult; lidské chromozomy, pár 5; genová přestavba; Chromosomes, Human, Pair 5